Challenges of inserting SMEs in global production networks: An analysis in the context of exploration of mineral resources in developing countries: Natural Sciences and Environment - Macuácua, Valentim; Mahaluça, Filipe; Maite, Anatólia; Moiana, Carla (Revista da UI_IPSantarém, 2022)
This article sought, through the analysis of bibliographic material (scientific articles) available, to identify and discuss the main challenges around the insertion of SMEs in global production networks in the extractive industry in developing countries. The discussions generated reflections on the positioning that developing countries and local SMEs should take in order to be an active part in promoting and improving their global competitiveness. As results, the following were identified as the main challenges for the integration of SMEs in global networks: (i) inexistence or inefficiency of local content laws (where they exist); (ii) lack of substantial operational and fixed capital to exercise several large-scale business activities; (iii) lack of international certification of quality in the services provided; (iv) weak technological innovation and skilled labour. And in view of the obstacles, it was observed that the competitiveness of SMEs in all its scope, requires external help, i.e. it needs a long-term strategic look either from the government alone or from the government associated with other stakeholder (s), in order to empower them, instilling the adoption of high performance standards, aiming to maximize the participation of domestic industry in the deployment of natural resource extraction projects. On the other hand, SMEs must restructure themselves, from the point of view of management and business strategy, because their effective integration into global production networks and global value chains requires profound changes, in terms of adopting technologies, organizational changes, and adopting strategies for local integration in supply networks, clusters.